PERBANDINGAN METODE DISKUSI KELOMPOK DAN METODE CERAMAH TERHADAP HASIL PEMBELAJARAN BIDANG STUDI EKONOMI DI SMA N 8 KOTA JAMBI - Lismaida Panggabean, Lili Andriani (SJEE (Scientific Journals of Economic Education), 2020)
Abstract This study aims to determine (1) Is there a difference in the average economic learning outcomes of students whose learning uses the group discussion method, (2) Is there a difference in the average economic learning outcomes in students whose learning uses the lecture method, and (3) Is there a comparison of economic learning outcomes in students whose learning uses the group discussion method with students whose learning uses the lecture method. Research results explained: Student learning outcomes in Economics subjects taught using group discussion methods obtain an average count of 57.56. And, Student learning outcomes in economics taught by the lecture method obtained an average count of 37.69. Thus, Student learning outcomes in Economics subjects taught using lecture learning methods are higher than student learning outcomes in Economics subjects taught by using group discussions with Sig. 0.025 <0.05. Keywords: Group Discussion, Lecture, Learning Outcomes